Hypothesis: A single dose of an anxiolitic may prevent unnecessary visits to the emergency room during blood pressure elevations. (March 2016) - Tandeter, Howard
Abstract: Blood pressure (BP) monitoring devices are very commonly used by the general public for self-measurement. Approximately 19% of people using these devises check their BP every day or almost every day and only one third use them because their doctor recommended it. Measurement often causes anxiety and anxiety increases blood pressure in the short term. Elderly patients often visit the emergency room (ER) due to these BP elevations. Almost 10% of patients presenting to ERs complained of high BP, and between 50–75% of them receive antihypertensive drugs (sometimes with serious adverse effects) despite the fact that only 7.5% are classified as hypertensive emergencies, and only 2.8% are at risk of serious outcome. Two studies suggested the use of anxiolitics in the treatment of excessive hypertension. When compared to captopril, treatment with diazepam or alprazolam showed to be effective in lowering BP, with no significant difference between the two groups. We therefore suggest that patients with acute elevations of BP (measured at home) try an anxiolytic before deciding to go to the ER. Patients in which BP lowers with the use of tranquilizers do not need to go to the ER. We also suggest using this strategy in patients visiting community clinics and ER for the same reason. Our hypothesis is that by using our suggestions there will be a significant reduction in the number of unnecessary visits to the ER, the use of medication that may produce serious adverse effects, and an important health cost reduction, without increasing the risk for patients (a 10% reduction of ER visits may save up to 300 million dollars/year in the US alone and prevent unnecessary use of medical facilities and manpower).